The Gestational age, Level of education, Living Place and Working status As the Determinant Factors of Dental Caries among Pregnant Women in Indonesia - Kamil, Alifya Andra; Bakar, Abu; Ningrum, Valendriyani (Universitas Baiturrahmah, 2024)
Dental caries is a major dental and oral health problem especially in pregnant woman. The physiological and hormonal changes during pregnancy may contribute to the incidence of dental caries. The aim of this study was to analyze the determinant caries in pregnant women in Indonesia based on Riskesdas 2018. The study was a cross sectional survey and used the secondary data sourced from Riskesdas 2018. The population in the study were all pregnant women from the Riskesdas team in 2018 totaling 519 samples using the PPS (probability proportional to size) - linear systematic sampling method, with two stage sampling. The statistical analysis using Chi-square test and multiple logistic regression test. The study showed the significant relationship between gestational age, level of education, place of the residence and working status and the incidence of dental caries in pregnant women in Indonesia (p<0.05). The study concluded that several factors had a significant relationship with the in incidence of caries among pregnant women in Indonesia.